A systematic review to establish health-related quality-of-life domains for intervention targets in cancer cachexia. Issue 3 (18th June 2014) - Wheelwright, S J; Darlington, A-S; Hopkinson, J B; Fitzsimmons, D; White, A; Johnson, C D
Abstract : Objectives: To develop a model of the impact of cancer cachexia on patients by identifying the relevant health-related quality-of-life (HRQOL) issues, and to use the model to identify opportunities for intervention. Methods: Standard systematic review methods were followed to identify papers which included direct quotes from cancer patients with cachexia or problems with eating or weight loss. Following thematic synthesis methodology, the quotes were coded, and themes and metathemes were extracted. The metathemes were used to develop a model of the patient's experience of cachexia. Results: 18 relevant papers were identified which, in total, contained interviews with more than 250 patients. 226 patient quotes were extracted from the papers and 171 codes. 26 themes and 8 metathemes were formulated. The model developed from the metathemes demonstrated a direct link between eating and food problems and negative emotions and also a link mediated by the associated physical decline. These links provide opportunities for interventions. Conclusions: There are a vast number of HRQOL issues associated with cancer cachexia as identified from patients' own words. The model generated from these issues indicates that relationships, coping and knowledge of the condition are important components of new psychosocial interventions.